Assessing the validity of Society of Thoracic Surgeons (STS) score in predicting stroke risk among patients undergoing cardiothoracic surgery at a tertiary hospital in Pakistan: a retrospective cohort study - Javerya Hassan; Namra Usman; Muhammad Salman; Arshan Ali; Maryam Shaukat; Hana Khan; Ahmed Raheem; Hasanat Sharif (Journal of Cardiothoracic Surgery)
Abstract Background Postoperative stroke is one of the most serious consequences of cardiac surgery. Morbidity risk assessment is critical for preoperative risk assessments and resource allocation. In this article, we aim to investigate the predictive value of Society of Thoracic Surgeons (STS) score’s effectiveness in stroke risk in cardiothoracic surgery patients in our population. Methods This retrospective cohort study was conducted at Aga Khan University Hospital (AKUH) using a consecutive sampling technique. The study included all eligible patients aged 18 years or older who underwent cardiac surgical procedures between January 2010 and December 2016. Of the 3,898 patients initially identified, 814 records were excluded due to incomplete data or pre-existing conditions. Statistical analyses, including chi-square tests, t-tests, and logistic regression, were performed to identify significant predictors of stroke. Prediction accuracy was assessed using a Receiver Operating Characteristic (ROC) curve, with Youden’s J statistic employed to determine optimal sensitivity and specificity thresholds. Results Out of 3,084 patients, 52 (1.7%) experienced a postoperative stroke. Stroke patients were significantly older (mean age 62.8 years vs. 57.7 years). They also had higher white blood cell count (10.7 ± 5.1 vs. 9.3 ± 3.3) and a longer history of myocardial infarction (9.2 ± 9.3 years vs. 6.9 ± 7.6 years). Cardiovascular interventions (15.4% vs. 7.7%), postoperative congestive heart failure (21.1% vs. 7.3%), and use of inotropes (5.8% vs. 1.6%) were more prevalent in stroke patients. Emergent surgical status (19.2% vs. 13.4%) and complications such as dialysis, prolonged ventilation, and intra-aortic balloon pump use were also significantly higher. The predictive model demonstrated strong accuracy in predicting postoperative stroke (AUC: 0.841, CI: 0.794–0.888). The ROC analysis for the STS stroke model showed high sensitivity (90.4%) and negative predictive value (99.7%), with moderate specificity (64.3%) and overall accuracy (64.8%), indicating excellent performance in ruling out stroke but moderate reliability in identifying positive cases. Conclusion The STS risk score demonstrated strong predictive accuracy for postoperative stroke risk in cardiothoracic surgery patients, effectively incorporating clinical factors already accounted for in the comprehensive set of 70 variables used in its calculation.